Banking and Finance - Haron, Razali; Md Husin, Maizaitulaidawati; Murg, Michael (IntechOpen, 2020)
The banking and finance industry plays a significant role in the economy of a nation. As such, continuous research and up-to-date feeds are necessary for it to stay competitive and resilient. Due to its revolving and dynamic nature as well as its significance and interlinkages with other industries, a well-functioning banking and finance system is vital in safeguarding the interest of all stakeholders. Banking and Finance covers a wide range of essential topics highlighting major issues related to banking and finance. The book is rich with empirical evidence, scientific researches, best practices, and recommendations, making it a compact yet handy reference for readers, especially those who are in the field of banking and finance.